The influence of liquidity, leverage, and profitability on dividend policy in manufacturing companies listed on the Indonesian stock exchange moderated by good corporate governance - Gumelar, Arya; Setijaningsih, Herlin Tundjung; Hendrian, Hendrian (Institute of Computer Science (IOCS), 2024)
This research aims to determine the moderated influence of liquidity, leverage, and profitability on dividend policy in manufacturing companies listed on the Indonesian Stock Exchange Moderated by Good Corporate Governance. This type of research is quantitative methods. Population in this research involved manufacturing companies listed on the Indonesia Stock Exchange for the 2015-2019 period, totaling 118 companies. Sampling process was taken using the purposive sampling. The data analysis technique used the Eviews version 9 program with multiple linear regression analysis techniques. According to the research findings, it can be concluded that liquidity and leverage influence policy dividend. Meanwhile, Good Corporate Governance and leverage are unable to moderate the influence of liquidity on dividend policy. Profitability is able to moderate the influence of liquidity on dividend policy. Then, GCG can strengthen the correlation between profitability and dividend policy.